2012
DOI: 10.1016/j.aim.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Regularity and rigidity of asymptotically hyperbolic manifolds

Abstract: In this paper, we study some intrinsic characterization of conformally compact manifolds. We show that, if a complete Riemannian manifold admits an essential set and its curvature tends to −1 at infinity in certain rate, then it is conformally compactifiable and the compactified metrics can enjoy some regularity at infinity. As consequences we prove some rigidity theorems for complete manifolds whose curvature tends to the hyperbolic one in a rate greater than 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…These coordinates enjoy a nice property we shall exploit in Section 5: we remark that they satisfy a certain Neumann condition at infinity. A similar idea was already present in an implicit form in [27,Section 3], where they construct even harmonic charts (with respect to the metric g) on the double of M. In all that follows we select a pointp 0 ∈ M and modified Fermi coordinate charts x in a neighborhood U ofp 0 as we constructed in the previous section such that x p 0 = 0 so that = t −1 x form a coordinate system in a neighborhood ofp 0 in M. Up to a linear redefinition of the coordinates x , we can assume that g p 0 = .…”
Section: Construction Of Harmonic Chartsmentioning
confidence: 67%
See 2 more Smart Citations
“…These coordinates enjoy a nice property we shall exploit in Section 5: we remark that they satisfy a certain Neumann condition at infinity. A similar idea was already present in an implicit form in [27,Section 3], where they construct even harmonic charts (with respect to the metric g) on the double of M. In all that follows we select a pointp 0 ∈ M and modified Fermi coordinate charts x in a neighborhood U ofp 0 as we constructed in the previous section such that x p 0 = 0 so that = t −1 x form a coordinate system in a neighborhood ofp 0 in M. Up to a linear redefinition of the coordinates x , we can assume that g p 0 = .…”
Section: Construction Of Harmonic Chartsmentioning
confidence: 67%
“…This idea was also employed in [27]. where H = n + O e −as is the mean curvature of the level sets of s (see Proposition 2.9).…”
Section: Construction Of a New Conformal Factormentioning
confidence: 95%
See 1 more Smart Citation
“…Fortunately, we do have intrinsic definition for conformally compact manifolds, for details, please see 24 and. 30 Secondly, for a C k,μ , k ≥ 0, conformally compact manifold, the defining function may not be unique.…”
Section: Introductionmentioning
confidence: 99%
“…The first author [3] showed that if (M, g) is a noncompact Riemannian manifold with an essential subset K and sectional curvatures approaching −1 to order e −ωr with ω > 1, together with similar decay on the covariant derivative of the curvature, then g admits a C 0,1 conformal compactification. For related results, see [4,5,7,9].…”
Section: Introductionmentioning
confidence: 99%